Effect of Marketing Communication, Satisfaction and Advertising on Consumer Loyalty in PT. Prudential Life Insurance - Ivany Wendy; Muhammad Agung Anggoro; Chaty Chana Br Purba; Jessica Prita Hanny (Journal of Research in Business, Economics, and Education, 2021)
The success of the company in order to survive and win the current business competition is the support of the loyalty of consumers who continuously use the company's products for their daily needs. In order to optimally encourage and increase consumer loyalty, consistent efforts are needed from all employees by improving communication skills when marketing products, providing optimal satisfaction in accordance with consumer expectations and desires and conducting advertisements with the right media and at the right time. For this reason, the research is intended to examine and determine the effect of marketing communication, satisfaction and advertising partially and simultaneously on consumer loyalty. The research uses quantitative, the population is prudential customers who have used the product as many as 1,250 people and sampling with the Slovin formula so that the number of samples is 93 respondents. The analysis technique used is data quality test, F test, t test, classical assumptions and hypotheses and multiple linear regression. The test results show that partially marketing communication has a significant effect on loyalty, satisfaction and advertising has no significant effect on loyalty. Simultaneously, marketing communications, satisfaction and advertising have a significant effect on consumer loyalty. The ability of consumer loyalty can be explained by marketing communications, satisfaction and advertising by 45.1% and the remaining 54.9% is explained by other variables outside the scope of this study. Marketing communication, satisfaction and advertising have a strong enough correlation to loyalty.